Sacralization of L5 associated with low back pain (Bertolotti Syndrome) review of a clinical case from the radiological point of view: Bertolotti's Syndrome: Sacralization of L5 and lumbar pain, case report - Iñiguez-Guzmán, Carlos Alfredo (2023)
Bertolotti syndrome is defined as low back pain with or without radicular pain, associated with congenital anomaly in the vertebral morphology (transverse megapophyses with or without fusion with sacral wings or iliac crests), as a consequence of which osteodegenerative facet and disc changes are observed at levels above the transitional vertebra, although it can also manifest itself at the same level with extraforaminal compressive disc pathology. With the aim of presenting a case from the radiological point of view of sacralization of L5 associated with low back pain, we present a patient who presents low back pain for 3 months; it is exacerbated with flexor-extensor and rotational movements of the trunk, he suffers a fall from his own height so an anteroposterior (AP) study of the pelvis and lateral sacro-coccyx is requested where findings related to Bertolotti's Syndrome are observed. This syndrome should be considered in the differential diagnosis of patients with low back pain with or without radiculopathy. Keys words: Low Back Pain; Bertolotti´s syndrome; Technology, Radiologic.